2022
DOI: 10.3390/md20080477
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic Potential of Marine Bioactive Peptides against Human Immunodeficiency Virus: Recent Evidence, Challenges, and Future Trends

Abstract: Acquired immunodeficiency syndrome (AIDS) is a chronic and potentially fatal ailment caused by the human immunodeficiency virus (HIV) and remains a major health problem worldwide. In recent years, the research focus has shifted to a greater emphasis on complementing treatment regimens involving conventional antiretroviral (ARV) drug therapies with novel lead structures isolated from various marine organisms that have the potential to be utilized as therapeutics for the management of HIV-AIDS. The present revie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 158 publications
0
3
0
Order By: Relevance
“…Peptide drugs have the advantages of higher bioactivity, selectivity, permeability, target potency and safety compared with small-molecule and protein drugs 25 . Therefore, peptides have been widely used in the treatment of cancer, diabetes, acquired immunodeficiency syndrome and cardiovascular diseases 26 , 27 , 28 , 29 . Our previous studies revealed that the antioxidant peptide DR8 (DHNNPQIR-NH 2 ) derived from rapeseed protein showed low toxicity and an inhibitory effect on organ fibrosis, such as lung, kidney and liver fibrosis 30 , 31 , 32 .…”
Section: Introductionmentioning
confidence: 99%
“…Peptide drugs have the advantages of higher bioactivity, selectivity, permeability, target potency and safety compared with small-molecule and protein drugs 25 . Therefore, peptides have been widely used in the treatment of cancer, diabetes, acquired immunodeficiency syndrome and cardiovascular diseases 26 , 27 , 28 , 29 . Our previous studies revealed that the antioxidant peptide DR8 (DHNNPQIR-NH 2 ) derived from rapeseed protein showed low toxicity and an inhibitory effect on organ fibrosis, such as lung, kidney and liver fibrosis 30 , 31 , 32 .…”
Section: Introductionmentioning
confidence: 99%
“…Plants, or more precisely, plant-isolated bioactive compounds, are being used to lower oxidative stress and to aid the treatment of a range of disorders as their health-beneficial qualities become more widely acknowledged. Furthermore, this aim is more applicable to disorders that are caused by or are impacted by oxidative stress [ 8 , 9 , 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Marine species are abundant sources of bioactive substances with a wide range of structural variations and biological activity and are becoming increasingly significant as a source of novel bioactive compounds [19]. These peptides are reportedly found in sponges, ascidians, seaweed, and mollusks and exhibit a variety of pharmacological characteristics [20,21]. Bioactive peptides have been identified as certain protein fragments that have a favorable effect on physiological conditions or processes and may have a health-promoting effect [22].…”
Section: Introductionmentioning
confidence: 99%